Construction of a 3-year risk prediction model for developing diabetes in patients with pre-diabetes - Yang, Jianshu; Liu, Dan; Du, Qiaoqiao; Zhu, Jing; Lu, Li; Wu, Zhengyan; Zhang, Daiyi; Ji, Xiaodong; Zheng, Xiang (Frontiers in Endocrinology, 2024)
Objective To analyze the influencing factors for progression from the newly diagnosed patients with prediabetes (PreDM) to diabetes within 3 years and establish a prediction model to assess the 3-year risk of developing diabetes in patients with PreDM. Methods Subjects who were diagnosed with new-onset PreDM at the Physical Examination Center of the First Affiliated Hospital of Soochow University from October 1, 2015 to May 31, 2023 and completed the 3-year follow-up were selected as the study population. Data on gender, age, body mass index (BMI), waist circumference, etc. were collected. After 3 years of follow-up, subjects were divided into a diabetes group and a non-diabetes group. A prediction model based on logistic regression was established with nomogram drawn. The calibration was also depicted. Results Differences in 24 indicators, including gender, age, history of hypertension, fatty liver, BMI, waist circumference, systolic blood pressure, diastolic blood pressure, fasting blood glucose, HbA1c, etc. were significant between the diabetes and non-diabetes groups (P<0.05). Differences in smoking, creatinine and platelet count were not significant between the two groups (P>0.05). Logistic regression analysis results showed that ageing, elevated BMI, male gender, high fasting blood glucose, increased level of LDL-C, fatty liver, liver dysfunction were risk factors for progression from PreDM to diabetes within 3 years (P<0.05), while the level of HDL-C was a protective factor (P<0.05). The derived formula was: In(p/1-p)=0.181×age (40-54 years old)/0.973×age (55-74 years old)/1.868×age (≥75 years old)-0.192×gender (male)+0.151×blood glucose-0.538×BMI (24-28)-0.538×BMI (≥28)-0.109×HDL-C+0.021×LDL-C+0.365×fatty liver (yes)+0.444×liver dysfunction (yes)-10.038. The AUC of the model for predicting progression from PreDM to diabetes within 3 years was 0.787, indicating good predictive ability of the model. Conclusions The risk prediction model was reasonable and simple for evaluating the risk of patients with PreDM to develop into diabetes within 3 years .